Sperm cephalic vacuoles: new arguments for their non acrosomal origin in two cases of total globozoospermia. (19th September 2012) - Gatimel, N.; Léandri, R. D.; Foliguet, B.; Bujan, L.; Parinaud, J.
Summary To add new arguments concerning the origin of the sperm‐head vacuoles observed under high magnification with interference contrast microscopy, we carried out in two patients with total globozoospermia confirmed using transmission electron microscopy (TEM), a detailed sperm morphometric analysis with high magnification (×6000) under Nomarski contrast, an acrosomal status analysis (using fluorescent labelling with peanut agglutinin (PNA) lectins and anti‐CD46 antibodies) and a nuclear status analysis (using terminal deoxynucleotidyl transferase‐mediated dUTP nick‐end labelling assay TUNEL, sperm chromatin structure assay SCSA and aniline blue staining). Our two patients with globozoospermia had relative sperm vacuole areas of 6.3% and 5%, similar to those observed in a reference population of 12 fertile men (5.9%). TUNEL and SCSA assays gave normal results in both patients, although the percentage of immature nuclei using aniline blue staining was increased (27 and 46% for patient 1 and 2 respectively). Cytofluorescence and TEM analysis evidence differences between the two patients: although no acrosomal neither Golgi residue could be detected in patient 1, patient 2 had positive PNA lectin labelling for 9% of spermatozoa and Golgi residues were seen using electron microscopy. Unlike patient 1, a live birth could be obtained after intracytoplasmic sperm injection (ICSI) for patient 2. This descriptive study of two patients with total globozoospermia confirmed using TEM argue in favour of a deep analysis of total globozoospermia before assisted reproductive technology and provides further information on the non‐acrosomal origin of the sperm‐head vacuoles observed under high magnification.